2022
DOI: 10.1021/acs.jpcc.2c00091
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Metal–Insulator Transition in TiO2/VO2 Superlattices by Modifying the Layer Thickness or Inducing Defects

Abstract: Vanadium dioxide (VO2) is a thermochromic material that can be used in advanced applications such as smart energy-saving windows and other smart optical/electronic devices. However, obtaining a comfortable metal–insulator transition temperature while improving solar utilization in VO2 remains an unresolved question at both the fundamental and application levels of research. Although studies on designing TiO2/VO2 multilayers to address the above issues have been widely reported, the nature of the metal–insulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…So, here we have the So, when viewing along the [110] R zone-axis, we see a structure that is completely epitaxial and homogenous across the lamella, but, when viewing along [100/010] R , we always see different ori-entations of VO 2 on the two sides of the cracks. These observations validate previous studies of the cracks developing as a stress relaxation mechanism [44,45] -all these grains have exactly the same rutile structure above the transition temperature, but as the thin film cools down, M1 VO 2 grains with different orientations nucleate and propagate until they meet resulting in stress which is only able to relax due to the formation of cracks. Overall, the presence of deep cracks in samples on (001) substrate results in relatively poor MIT characteristics, and thus VO 2 on this substrate is not suitable for electronic applications unless the stress can be tuned by external mechanisms like doping, or caused to relax with features other than cracks.…”
Section: Vo 2 On Tio 2 (001)supporting
confidence: 88%
See 3 more Smart Citations
“…So, here we have the So, when viewing along the [110] R zone-axis, we see a structure that is completely epitaxial and homogenous across the lamella, but, when viewing along [100/010] R , we always see different ori-entations of VO 2 on the two sides of the cracks. These observations validate previous studies of the cracks developing as a stress relaxation mechanism [44,45] -all these grains have exactly the same rutile structure above the transition temperature, but as the thin film cools down, M1 VO 2 grains with different orientations nucleate and propagate until they meet resulting in stress which is only able to relax due to the formation of cracks. Overall, the presence of deep cracks in samples on (001) substrate results in relatively poor MIT characteristics, and thus VO 2 on this substrate is not suitable for electronic applications unless the stress can be tuned by external mechanisms like doping, or caused to relax with features other than cracks.…”
Section: Vo 2 On Tio 2 (001)supporting
confidence: 88%
“…Further studies are required to study the properties of these heterostructures since the MIT characteristics should be affected by this intermediate intermixing layer. [ 45 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the effective design of buffer materials and the integration of VO 2 into multilayer structures prepared on affordable commercial substrates must be studied. Titanium dioxide (TiO 2 ) has recently emerged as a promising candidate because of its rutile-phase crystal structure with small lattice mismatch and high visible–IR transmittance. Zhang et al found that using TiO 2 as a buffer layer improves the phase transition performance and IR solar modulation ability from 13 to 23% for VO 2 thin films deposited on glass substrates. However, even with the introduction of the TiO 2 buffer layer, a narrow thermal hysteresis loop ( H LW ) of the electro-optic thermochromism of the VO 2 thin film on the glass substrate was still unattainable, which is essential for high-speed optical switching device applications.…”
Section: Introductionmentioning
confidence: 99%